Transanal endorectal pull-through in children as the treatment for Hirschsprung’sd in Aceh, Indonesia - Isa, Muntadhar M.; Syahputra, Dian A.; Hutagalung, Muhammad Bayu Z. (International Surgery Journal, 2019)
Background: One-stage pull-through operation has become increasingly popular for the treatment of Hirschsprung’s disease. The advantages of total transanal pull-through include minimal resection of the dilated ganglionic part of the colon, shorter hospital stay, decreased total cost, lower risk of adhesive intestinal obstruction. Methods: A retrospective study of patients with HD underwent transanal endorectal pull-through (TERPT) procedure treated at Dr. Zainoel Abidin Hospital Banda Aceh, Indonesia between January 2010 – December 2013. We assessed patients characteristic, outcome and complication including Hirsch sprung associated enterocolitis (HAEC). Results: A total 77 patients were included in this study. The mean age was 13.01 months (range from 11 days – 8 years old). Most of the patients (55.8%) were male and female (44.2%). Clinical classification of HD: short segment 74 patients (96.1%) and ultra-short segment 3 patients (3.9%). The mean of bowel resection length in TERPT procedure was 18.64 cm (range from 7–25 cm). There is no mortality associated with TERPT procedure. Hirsch sprung associated enterocolitis (HAEC) occurred in 43 subjects (54.5%). Statistical analysis showed the significant relation between age at surgery and HAEC (p= 0.000) and no significant relationship between gender (p=0.425) and bowel resection length (p=0.780) with HAEC. Conclusions: Transanal endorectal pull-through procedure has been shown as an effective minimally invasive treatment in resolving obstructive symptoms in ultra–short segment of HD patients. The number of HAEC incidence among HD patients underwent TERPT significantly increased with older age of children.